Binder Free Modification of Glassy Carbon Electrode by Employing Reduced Graphene Oxide/ZnO Composite for Voltammetric Determination of Certain Nitroaromatics. Issue 2 (12th December 2017) - Mohammad, Akbar; Ahmad, Khursheed; Rajak, Richa; Mobin, Shaikh M.
Abstract: Reduced Graphene oxide/ZnO nanoflowers (rGO/ZnO‐NFs ) composite has been synthesized in‐situ using asymmetric Zn complex (1 ) as a single‐source molecular precursor (SSMP) withGO at 150 °C. TherGO/ZnO‐NFs composite was characterized by PXRD, UV‐ vis, SEM, EDX mapping, TEM and SAED pattern to confirm its purity and morphology. TherGO/ZnO‐NFs composite shows uniform distribution of nanoflowers on graphene sheets. The modified glassy carbon electrode (GCE ) was fabricated by drop wise layering of therGO/ZnO‐NFs composite at the surface of theGCE without using binder. The binder free modified electrode (GCE‐rGO/ZnO ) was explored for detection of nitroaromatics such as p ‐nitro‐phenol ( p ‐NP ), 2, 4‐dinitrophenol (2, 4‐DNP ), 2, 4‐dinitrotoluene (2, 4‐DNT ) and 2, 4, 6‐trinitrophenol (2, 4, 6‐TNP ). The fabricated sensor showed remarkable response for the both toxicants and explosives. The LOD, sensitivity and linear range for the studied toxicants and explosives were found to be in a good range: p ‐NP= 0.93 μM, 240 μA mM −1  cm −2 and 0.2–0.9 mM;2, 4‐DNP= 6.2 μM, 203 μA mM −1  cm −2 and 0.1–0.9 mM;2, 4‐DNT= 10 μM, 371 μA mM −1  cm −2 and 0.2–0.9 mM;2, 4, 6‐TNP= 16 μM, 514 μA mM −1  cm −2 and 0.2–0.9 mM, respectively. Abstract : A binder free electrode was fabricated usingrGO/ZnO‐NFs as a modifier and has been explored for the electrochemical detection of nitroaromatics. Fabricated sensor (GCE‐rGO/ZnO) has shown the remarkable low detection limit, considerably good sensitivity with high repeatability and stability towards the measured analytes.